Macroprudential Policy, Monetary Policy and Banking Sector Performance in Nigeria - Aliyu, Ahmed Alhaji; Eliphus, Jeffery; Imam, Rilwan Shehu; Adili, Mubarak Ahmad (Disclosure: Journal of Accounting and Finance, 2024)
This study examined the impact of macroprudential policy, monetary policy and banking sector performance in Nigeria. This study used ex post facto research design and secondary data from Quarter 1 2007 to Quarter 4 2022. Data were sourced from the International Monetary Fund, Central Bank of Nigeria, and World Bank Database. The study utilized ARDL-bound testing and ARDL-ECM to estimate the data. It was found that in the long run macro-prudential policy Capital Adequacy and Liquidity (Liquid Assets to Short-term Liabilities) have a positive relationship with banking sector performance in Nigeria. More so, Liquidity (Liquid Assets to Total Assets) and Asset Quality have a negative and significant relationship with banking sector performance in Nigeria. In addition, in the short-run, monetary policy tools were more effective and it was found that Exchange Rate and Monetary Policy Rates have a negative and significant relationship with banking sector performance in Nigeria, while Money Supply has a positive relationship with banking sector performance in Nigeria. It was concluded that macroprudential policy tends to be more effective on banking sector performance in Nigeria in the long run, while monetary policy tends to be effective in the short run. Hence, both policies complement each other rather than substitute in mitigating risks Inherent in banking sectors.